More comedies and tragedies - Lawrence, Julie Fain (One-hour Shakespeare, 2022)
"The One-Hour Shakespeare series is a collection of abridged versions of Shakespeare's plays, designed specifically to accommodate both small and large casts. This volume, More Comedies and Tragedies, includes the following plays: The Comedy of Errors, The Taming of the Shrew, Antony and Cleopatra, King Lear. These accessible and versatile scripts are supported by: an introduction with emphasis on the evolution of the series and the creative process of editing; the One-Hour projects in performance, a chapter on implementing money-saving ideas and suggestions for production, whether in or outside a classroom setting; specific lesson plans to incorporate these projects successfully into an academic course; and cross-gender casting suggestions. These supplementary materials make the plays valuable not only for actors, directors and professors, but for any environment, cast or purpose. Ideal for both academics and professionals, One-Hour Shakespeare is the perfect companion to teaching and staging the most universally read and performed playwright in history"--